TINGKAT PEMANFAATAN FASILITAS DASAR DAN FUNGSIONAL UNTUK PENINGKATAN PRODUKSI DI PANGKALAN PENDARATAN IKAN TANJUNGSARI KABUPATEN PEMALANG - Ardandi, Savino Nisen; Boesono, Herry; Rosyid, Abdul (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Fishing port is an important aspect in the development of fisheries. Fishing port is the place that made up the land and surrounding waters with certain limits as the governmental activities and the activities of the fishing business systems that are used as berths and loading and unloading of fish. The purpose of this study was to analyze the level of utilization of basic and functional facilities that exist in the Tanjungsari Fishing port. The method used in collecting data of this study is descriptive method and case studies. Descriptive method is a method of data collection surveys and direct observation in the field and do pangumpulan data by focusing on an intensive and detailed case. Based on the results obtained a conclusion that is basic and functional condition of the facility at Fish Landing Base Tanjungsari Pemalang in less optimal conditions. The utilization rate of basic facilities and functional Tanjungsari Fishing port as follows: The Land Use by 87%; cruise line by 89%; the dock by 90% and 83% of the auction building. Strategy to increase the utilization of basic facilities and is a functional Tanjungsari Fishing port opitimal use of basic facilities, functional and support in order to increase fish production; Provide counseling and socialization on a regular basis to business Tanjungsari fishery in relation to the increase in fish production; Improve fishing technology such as the use of GPS and Fishfinder to increase the catch.